Heat transfer to a catalytic multiphase dehydrogenation reactor - Willer, Miriam; Preuster, Patrick; Malgaretti, Paolo; Harting, Jens; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2024)
The release of hydrogen from liquid organic hydrogen carriers (LOHC) takes place in an endothermal dehydrogenation reaction that is accompanied by a strong volume expansion. This leads to complex hydrodynamic properties that change drastically along the reactor axis due to product gas evolution. Consequently, heat transfer into the catalytic fixed-bed exhibits a pronounced local dependency. For a better understanding of such multiphase dehydrogenation systems, we have performed heat transport measurements in the presence of the chemical reaction, namely during the dehydrogenation of perhydro benzyltoluene (H12-BT) and perhydro dibenzyltoluene (H18-DBT). The results reveal that overall heat transfer coefficients show a clear local dependency on the axial coordinate. Moreover, the two carriers were found to differ significantly in their thermal behavior. Based on a global analysis, two main regimes can be distinguished in the dehydrogenation reactor: 1.) With the LOHC mixture being primarily in the liquid phase, heat transport is dominated and intensified by the hydrogen release; 2.) With an increasing proportion of LOHC vapor in the reactor, the heat transport is dominated by the gas phase, resulting in significantly lower thermal parameters.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Dehydrogenation; Heat transfer; Hydrogen storage; LOHC; Multiphase system